Perbedaan Persepsi Antara Mahasiswa Dengan Mahasiswi Akuntansi Terhadap Profesi Akuntan (Studi Kasus di Universitas Sebelas Maret (UNS) dengan Universitas Muhammadiyah Surakarta (UMS)) - Yulianti, Septina; , Drs. Yuli Tri Cahyono , M.M., Akt., CA (2015)
This research to analyze whether there are different between boys and girls students of university perception of the accounting profession. Population in this study were under graduate students majoring in accounting at the first economy faculty in UNS and UMS who where devided into two groups, namely men and women. Method of data collection using questionnaires and hipothesis testing techniques used in this study is the Independent Sample Test. The result showed that no there were significant differences in perceptions between male and female student to the accounting profession. Keywords: accounting profession, male students, female students.